Análise fatorial para dados qualitativos ordinais - Lu, Ching Yu (Universidade Federal de São Carlos, 2021)
The use of the factor analysis is appropriate for quantitative data. Therefore, alternatives should be considered to use factor analysis with ordinal data. In this work, exploratory factor analysis for ordinal data is described. Specifically, we utilize special correlations such as Spearman and polychoric. Moreover, we apply exploratory factor analysis to dataset provided by the evaluation committee of the Federal University of São Carlos (CPA/UFSCar). The dataset was obtained by a questionnaire whose response scale is Likert type.
Factor analysis for ordinal qualitative data
Keywords: Análise fatorial exploratória; Análise fatorial para dados qualitativos; Correlação de Spearman; Correlação policórica; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::ANALISE MULTIVARIADA